Surface Modified Pinecone Shaped Hierarchical Structure Fluorinated Mesocarbon Microbeads for Ultrafast Discharge and Improved Electrochemical Performances. Issue 2 (1st January 2017) - Dai, Yang; Fang, Yuan; Cai, Sendan; Wu, Lijun; Yang, Weijing; Yan, Hao; Xie, Jingying; Zheng, Jin-Cheng; Takeuchi, Esther; Zhu, Yimei
Abstract : Among all primary lithium batteries, Li/CFx primary battery possesses the highest energy density of 2180 Wh kg −1 . However, a key limitation is its poor rate capability because the cathode material CFx is intrinsically a poor electronic conductor. Here, we developed a so-called "doing subtraction" method to modify the pinecone shaped fluorinated mesocarbon microbead (F-MCMB). The modified fluorinated mesocarbon microbead (MF-MCMB), manifests the advantage of open-framed structure, possesses good electronic conductivity and removes transport barrier for lithium ions. Thus, high capacity performance and excellent rate capability without compromising capacity can be obtained. A capacity of 343 mAhg −1 and a maximum power density of 54600 W kg −1 are realized at an ultrafast rate of 40 C (28A g −1 ). In addition, the MF-MCMB cathode does not show any voltage delay even at 5C during the discharge, which is a remarkable improvement over the state-of-the-art CFx materials.